2020
DOI: 10.3390/sym12010156
|View full text |Cite
|
Sign up to set email alerts
|

Family Symmetries and Multi Higgs Doublet Models

Abstract: Imposing a family symmetry on the Standard Model in order to reduce the number of its free parameters, due to the Schur’s Lemma, requires an explicit breaking of this symmetry. To avoid the need for this symmetry to break, additional Higgs doublets can be introduced. In such an extension of the Standard Model, we investigate family symmetries of the Yukawa Lagrangian. We find that adding a second Higgs doublet (2HDM) does not help, at least for finite subgroups of the U ( 3 ) group up to the order of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Explicit flavor symmetry breaking can be avoided in the presence of Higgs fields that transform under G. Two-Higgs doublet models [15] are obvious candidates to investigate that principle. In [16] and [17] non-Abelian groups have been identified providing lepton masses and a mixing matrix, but these were not in agreement with experiment. Although the implied lepton masses of the model were found nondegenerate, the implied mixing matrices appeared to be always monomial.…”
mentioning
confidence: 71%
“…Explicit flavor symmetry breaking can be avoided in the presence of Higgs fields that transform under G. Two-Higgs doublet models [15] are obvious candidates to investigate that principle. In [16] and [17] non-Abelian groups have been identified providing lepton masses and a mixing matrix, but these were not in agreement with experiment. Although the implied lepton masses of the model were found nondegenerate, the implied mixing matrices appeared to be always monomial.…”
mentioning
confidence: 71%
“…In case A = χ 4 and B = χ 4 it is found that A ⊗ B = (9, −6, 0, 3, −6). For H = χ 4 it follows from Equation (19) 4 ) is a candidate character triplet to define a symmetry of the charged-lepton mass term. One more triplet, (A, B, H) = (χ 4 , χ 4 , χ 5 ) appears viable too.…”
Section: Methods To Find Relations Among the Lepton Mass And Mixing P...mentioning
confidence: 99%
“…The aforementioned explicit flavor symmetry breakdown in the Yukawa sector can be avoided in the presence of Higgs fields (causing spontaneous symmetry breaking) that transform under G. Two-Higgs doublet models (2HDM) [17] are obvious candidates to investigate that principle. In [18,19] non-Abelian groups that have two-and threedimensional irreducible representations have been investigated. The lepton masses and the angles of the mixing matrix resulting from the assumed discrete symmetry were found, but the agreement with the experimental data was not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned explicit flavor symmetry breakdown in the Yukawa sector can be avoided in the presence of Higgs fields (causing spontaneous symmetry breaking) that transform under G. Two-Higgs doublet models (2HDM) [17] are obvious candidates to investigate that principle. In [18] and [19] non-Abelian groups that have two-and three-dimensional irreducible representations have been investigated. The lepton masses and the angles of the mixing matrix resulting from the assumed discrete symmetry were found, but the agreement with the experimental data was not satisfactory.…”
Section: Introductionmentioning
confidence: 99%